Factors of the Kaingang culture which influence care for the older adult: the view of the health professional - Leidyani Karina Rissardo; Aline Cardoso Machado Moliterno; Ana Carla Borghi; Lígia Carreira (Universidade de São Paulo, 2013)
OBJECTIVE: to describe the health professionals' perception in relation to the factors of the Kaingang culture which influence the undertaking of healthcare practices with the elders in this ethnic group. METHOD: descriptive research with a qualitative approach, grounded in the ethnographic method, undertaken with ten health professionals who work in the Indigenous Territory in Faxinal, in the Brazilian state of Paraná. The data was collected in the period November 2010 to February 2012 through interviews and participant observation, and was analyzed in the light of the Transcultural Nursing Theory. RESULTS: evidence was found that the Kaingang culture has a strong influence on the professional care for the older adult, principally due to the cultural strangeness of certain customs, aspects which limit the health care for such older adults being listed. CONCLUSION: knowledge of the influences on the care can contribute to the forming of a framework of information relevant to the professional in the provision of care for the Kaingang older adults.